Learning Environment Preference for a Physical Classroom: A Student Survey - Anuar A.; Jamaluddin J.E.; Ibrahim Z. (Springer Science and Business Media Deutschland GmbH, 2025)
The learning environment is one of the important factors in making the learning process effective. In the post-pandemic era, as the majority of the learning in higher learning institution reverted to physical face-to-face, the physical classroom environment or space has become important again. A cross-sectional online survey was conducted among students at Universiti Tenaga Nasional (UNITEN) between May 25, 2023, and May 31, 2023. The main objective of this survey was to know more on what the student?s preference on features of physical classroom and their learning environment are, especially after returning to on-campus learning. Descriptive analysis was used to evaluate the rating given by the students. The survey was opened to all students, and 635 responses (62.8% male, 37.2% female) were collected. For the rating of existing classrooms, the students prefer a flat-type spacious class with mobile chair and table. Most of the respondents indicated that this class type is comfortable (76%), having good seating arrangements (73%), and having good interior design/ambience (68%). As for the future classroom, the highly wanted features are classrooms having good air flow and circulation (86.5%), followed by comfortable seating (84.4%), having good acoustics attribute (80.2%), spacious room (74.2%), and moveable chair/table (68.2%). The outcome of this study should provide a good guide when designing classrooms in the future. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.